2001
DOI: 10.1002/ana.1100
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Creutzfeldt‐Jakob disease in a young Dutch valine homozygote: Atypical molecular phenotype

Abstract: A case of sporadic Creutzfeldt-Jakob disease (sCJD) is described in a young Dutch protein prion gene (PRNP) codon 129 valine homozygote. Certain clinical and molecular features of this case overlap those of variant CJD. The case highlights possible difficulties in the differential diagnosis of vCJD and the more rare sCJD subtypes based on molecular features alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
1
14
2
Order By: Relevance
“…6,11 The means by which such conformational difference is detected is somewhat indirect; relying on the action of proteases, primarily proteinase K, to degrade the normal A complication has recently arisen with the finding that both type 1 and type 2 can co-exist in the brains of patients with sCJD. 2,[5][6][7][8] More recently this same phenomenon has been demonstrated in patients with iatrogenically acquired and familial forms of human prion disease. 9,10 The existence of this phenomenon is now beyond doubt but its prevalence and its biological significance remain a matter of debate.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…6,11 The means by which such conformational difference is detected is somewhat indirect; relying on the action of proteases, primarily proteinase K, to degrade the normal A complication has recently arisen with the finding that both type 1 and type 2 can co-exist in the brains of patients with sCJD. 2,[5][6][7][8] More recently this same phenomenon has been demonstrated in patients with iatrogenically acquired and familial forms of human prion disease. 9,10 The existence of this phenomenon is now beyond doubt but its prevalence and its biological significance remain a matter of debate.…”
Section: Discussionmentioning
confidence: 61%
“…4 Recent reports show that certain cases of sCJD contain both type 1 and 2 in the same brain. [5][6][7][8] Regional variation in PrP Sc type has subsequently been reported in iatrogenic CJD 9 and in familial CJD, 10 suggesting that co-occurrence of different PrP Sc types is perhaps the rule in CJD. In contrast, all of the available evidence so far has suggested that the variant CJD (vCJD) brain contains a single type, which has been interpreted to reflect infection of susceptible individuals by a single defined pathogen, namely bovine spongiform encephalopathy (BSE).…”
mentioning
confidence: 99%
“…The only other published observation of this kind is, to our knowledge, the report of a sporadic CJD in a valine homozygote at codon 129. 5 In this case, the glycoform ratio of PrP sc from postmortem left frontal cortex contrasted starkly with that previously seen at biopsy of the right frontal cortex. In a previous report, Parchi and colleagues examined the regional variation of PrP sc in nine patients with FFI.…”
contrasting
confidence: 49%
“…In addition, the positive rate of the FDC assay was as high as that of intracerebral transmission in the present study. Therefore, the FDC assay after intraperitoneal inoculation of patient materials to Ki-Bov/Bov may help in the differential diagnosis of vCJD when atypical cases emerge in CJD surveillance (33,34).…”
Section: Discussionmentioning
confidence: 99%